Analisis Politik Hukum Undang-Undang Nomor 23 Tahun 2019 tentang Pengelolaan Sumber Daya Nasional Untuk Pertahanan Negara - Dede Anggara Saputra (Lex Renaissance, 2020)
This study aims to analyze the legal politics of Law Number 23 of 2019 on Management of National Resources for National Defense. The legal issues presented in this study are the political direction of Law Number 23 of 2019 on the Management of National Resources for National Defense and its implications for the people. This is a normative legal research, which the results conclude that the birth of the a quo Law is motivated by a situation to strengthen the national defense in the face of threats through the universal people's defense system. The legal political direction of the a quo Law is to realize the upholding of state sovereignty, maintaining territorial integrity, and the safety of the entire nation from all forms of threats. In addition, a number of principles listed as the basis in the a quo Law are quite manifest in several articles. However, these principles are then reduced by the tendency of the material content of the a quo Law which has the nuances of violating human rights, overcriminalization, being less accommodating to current threat conditions, as well as creating the potential for misuse in its funding.